Empowering Consumers in Food Value Chains: Preliminary Insights from an Investigation into the Development of Tools for Food Safety - Bamgboje-Ayodele, Adeola; Ellis, Leonie; Turner, Paul (ACIS, 2014)
Changes in the purchasing preferences, attitudes and behaviours of many consumers towards food has highlighted the increased appetite for more and better quality information on the safety, quality and provenance of food products and on the sustainability of food production.This research-in-progress paper presents preliminary insights from an investigation into mechanisms for premium food producers to develop information services to both better understand and enhance food consumers’ decision-making on food and food value chains based on quality, safety and provenance. Following a review of key literature on consumer technology adoption and use for decision-making, the paper outlines the conceptual framework and methodology being used in the investigation and reports on insights generated from the first industry case-study. The paper highlights continuing evidence gaps and outlines next steps towards the conduct of consumer focused data collection and analysis aimed at developing tools to enhance food safety during food recall incidents.